Regulation of an amiloride-sensitive Na(+)-permeable channel by a β(2)-adrenergic agonist, cytosolic Ca(2+) and Cl(−) in fetal rat alveolar epithelium - Marunaka, Yoshinori (Blackwell Science Inc, 1999)
1. In cell-attached patches formed on the apical membrane of fetal alveolar epithelium, terbutaline (a specific β(2)-adrenergic agonist) increased the open probability (P(o)) of an amiloride-sensitive Na(+)-permeable non-selective cation (NSC) channel (control, 0.03 ± 0.04; terbutaline, 0.62 ± 0.18; n = 8, P < 0.00001) by increasing the mean open time 100-fold without any significant change in the mean closed time and without any change in the single channel conductance (control, 27.8 ± 2.3 pS; terbutaline, 28.2 ± 2.1 pS; n = 8). 2. The P(o) of the unstimulated channel increased when the apical membrane was depolarized due to a decrease in the closing rate and an increase in the opening rate, while the P(o) of the terbutaline-stimulated channel did not depend on the membrane potential. 3. Increased cytosolic [Ca(2+)] also increased the P(o) of the channel in a manner consistent with one Ca(2+)-binding site on the cytosolic surface of the channel. Terbutaline increased the sensitivity of the channel to cytosolic Ca(2+) by shifting the concentration of cytosolic Ca(2+) ([Ca(2+)](c)) required for half-maximal activation to a lower [Ca(2+)](c) value, leading to an increase in P(o). 4. An increase in the cytosolic Cl(−) concentration ([Cl(−)](c)) decreased the P(o) of the channel consistent with two Cl(−)-binding sites by increasing the closing rate without any significant change in the opening rate. Terbutaline increased P(o) by reducing the effect of cytosolic Cl(−) to promote channel closing. 5. Taken together, these observations indicate that terbutaline activates a Ca(2+)-activated, Cl(−)-inhibitable, amiloride-sensitive, Na(+)-permeable NSC channel in fetal rat alveolar epithelium in two ways: first, through an increase in Ca(2+) sensitivity, and second, through a reduction in the effect of cytosolic Cl(−) to promote channel closing.